Effect of probiotics on small intestinal bacterial overgrowth in patients with gastric and colorectal cancer - Liang, Sufang; Xu, Lin; Zhang, Dongsheng; Wu, Zhenjun (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Small intestinal bacterial overgrowth (SIBO) may be related to the presence of gastrointestinal cancer. The exact link, however, between SIBO and cancer prevalence as well as cancer symptoms remains unclear, especially in Asian populations. In addition, there is a paucity of data documenting the influence of probiotic treatment of SIBO on cancer symptoms. Here, the aims were to correlate the presence of SIBO with cancer prevalence and cancer symptoms, as well as to investigate the effect of probiotic intervention on SIBO and cancer symptoms. Materials and Methods: Employing a case-control design, 112 gastric and 88 colorectal cancer patients were evaluated. Questionnaires were used to assess gastrointestinal symptoms and a glucose-H2-breath test (GHBT) was used to determine SIBO status. Patients with SIBO were administered Bifidobacterium triple viable capsule therapy or placebo. Subsequently, SIBO status and gastrointestinal symptom scores were reanalyzed. Results: In our study group, 63.0% of patients versus 16.3% of controls was tested positive for SIBO. In patients with cancer, SIBO was associated with proton pump inhibitor (PPI) use. Bifidobacterium triple viable capsule was effective in combating SIBO and was associated with a significant improvement in gastrointestinal cancer-related symptoms. Conclusion: In a Chinese cohort, SIBO is associated with gastrointestinal cancer. Based on the preliminary intervention study, we conclude that probiotic intervention combats SIBO in patients with gastrointestinal cancer and alleviates its symptoms.